Lack of Effective Control on Killer Acquisitions in the Big Tech Market under EU Framework: Rethinking of EUMR Rules? - Ahmet Selim Kızılay (Public and Private International Law Bulletin)
Antitrust enforcement comprises a wide body of rules to control undertakings operating in specific markets. This study examines whether any rethinking of the EU Merger Regulation rules is required to capture transactions escaping antitrust scrutiny, also referred to as “killer acquisitions” where large incumbents buy out innovative start-ups with the principal incentive to pre-empt competition restraint in the future. Existing measures aim to exercise a sort of control for acquisitions that fly under the antitrust radar and fall short of addressing and preventing “killer” intentions occurring in specific product and service markets. It will further call for reform on the approach that competition authorities take while reviewing merger filings to adjust the tools for a better fit to scrutinize such killing strategies which would potentially result in harmful effects to the innovative market structure and eventually to consumer welfare. With the new generation of products in the digital markets, the traditional rules of competition law might fall short of effective solutions. Once given the theoretical background and the measures adopted at the Member State level and recent calls for strengthening competition law tools at the EU level, we aim to demonstrate the inadequacy of the existing rules to address the need for closer scrutiny over the tech giants, i.e., the GAFAM five, and we suggest adapted tools to ensure fair competition.